2019
DOI: 10.1186/s12871-019-0875-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastometry guided blood-component therapy after cardiac surgery: a randomized study

Abstract: BackgroundSignificant bleeding is a well known complication after cardiac surgical procedures and is associated with worse outcome. Thrombelastometry (ROTEM®) allows point-of-care testing of the coagulation status but only limited data is available yet. The aim was to evaluate the ROTEM®-guided blood component therapy in a randomized trial.MethodsIn case of significant postoperative bleeding (> 200 ml/h) following elective isolated or combined cardiac surgical procedures (including 14% re-do procedures and 4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…39,40,61,[72][73][74][75] Moreover, most of the outcome studies have reported only a modest benefit of using viscoelastic POC devices, typically limited to a small reduction in blood loss or blood transfusion. [28][29][30][31][32][33][34][35][36][37]62,63,[76][77][78][79][80] Most reviews of viscoelastic POC tests have also commented on the low quality of evidence currently available, and have called for further studies of their accuracy and role.…”
Section: Discussionmentioning
confidence: 99%
“…39,40,61,[72][73][74][75] Moreover, most of the outcome studies have reported only a modest benefit of using viscoelastic POC devices, typically limited to a small reduction in blood loss or blood transfusion. [28][29][30][31][32][33][34][35][36][37]62,63,[76][77][78][79][80] Most reviews of viscoelastic POC tests have also commented on the low quality of evidence currently available, and have called for further studies of their accuracy and role.…”
Section: Discussionmentioning
confidence: 99%
“…Haensig et al [12] also reported that POC was effective if CPB time was > 115 min. However, Girdauskas et al [13] reported that POC was more useful for the surgery with deep hypothermic circulatory arrest (DHCA), with an average CPB time of approximately 200 min.…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative bleeding following cardiothoracic procedures remains an important concern with multiple avenues of investigation continuing to assess factors predisposing and potentially influencing the severity of this adverse event. Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; 33 36 direct linkage of postoperative cardiac surgical bleeding with increased cost; 4 , 5 safe and efficacious use of postoperative fibrinogen concentrates; 37 , 38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39 , 40 transfusion reductions associated with the use of prothrombin complex concentrate; 41 , 42 morbidity associated with reoperation for bleeding following cardiac surgery; 3 , 43 , 44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45 , 46 contribution of albumin/gelatin to postoperative bleeding; 47 49 advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; 50 52 benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53 , 54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55 , 56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7 , 57 …”
Section: Discussionmentioning
confidence: 99%